Effect of a Dihydrobenzofuran Derivative on Lipid Hydroperoxide-Induced Rabbit Corneal Neovascularization - Hirotsugu Ogura; Takako Nakanishi-Ueda; Toshihiko Ueda; Shinichi Iwai; Seiichi Uchida; Yuta Saito; Yoko Taguchi; Hajime Yasuhara; Donald Armstrong; Katsuji Oguchi; Ryohei Koide (Elsevier, 2007)
The aim of this study was to investigate the effect of A-3922, a dihydrobenzofuran derivative, on linoleic acid hydroperoxide (LHP)-induced corneal neovascularization (NV) in a rabbit model. Male New Zealand rabbits Received intraperitoneal (i.p.) injections of 10 or 30 mg/kg per day A-3922 or its vehicle as control for 3 days. One day after i.p. injections, LHP was injected with a 30-gauge needle into the corneal stroma of the superior quadrant 4.5-mm below the limbus. Photographs of the vessels were taken for digital analysis with a surgical microscope. Vascular endothelial growth factor (VEGF) was measured using an immunoassay kit, and matrix metalloproteinase (MMP)-9 was measured by gelatin zymography in corneal samples. At 7 days post-LHP injection, the total vessel length was 26.7 ± 3.8 mm in the control animals (n = 8), 16.1 ± 0.8 mm in the A-3922 (10 mg/kg)-treated group (n = 5), and 11.4 ± 2.1 mm in the 30 mg/kg group (n = 8, P<0.01 vs control), respectively. After LHP injection, the content of VEGF and MMP-9 activity were increased in the superior cornea, but these were not influenced by A-3922 treatments. These results indicate that LHP-induced corneal NV is inhibited by treatment with A-3922 and therefore may represent a potential pharmacological intervention for ocular neovascularization disorders. Keywords:: neovascularization, lipid hydroperoxide, dihydrobenzofuran derivative, vascular endothelial growth factor (VEGF), matrix metalloproteinase (MMP)